An attenuated multiple genetic mutant of Mycoplasma pneumoniae imparts good immuno-protection against M. pneumoniae pneumonia in BALB/c mice. (April 2022) - Jiang, Zhulin; Zhou, Runjie; Leung, Polly H.M.; Deng, Zhongliang; Li, Shuihong
Abstract: Mycoplasma pneumoniae ( M. pneumoniae ) is the causative agent of both upper and lower respiratory infections that can lead to pneumonia, extrapulmonary complications and devastating sequela. With the increasing rate of macrolide-resistant strains, the severe clinical consequence of refractory mycoplasma pneumonia in children health calls for the need of vaccine research for this pathogen. In this report, the immunomodulatory effectiveness of a live attenuated M. pneumoniae vaccine was evaluated. The vaccine strain was a mutant strain of M. pneumoniae, MUT129, obtained after multiple passages of M129 strain in PPLO broth. The SNP/InDel detection results showed that mutations were present in genes encoding the adhesion organelle-associated proteins and lipoproteins of M. pneumoniae MUT129. Upon intranasal challenge of BALB/c mice with 1 × 10 7  CFU of MUT129, there were very small amount of Mycoplasma antigens and almost no M. pneumoniae present in the lung tissues of BALB/c mice. Besides, there was almost no inflammatory cell infiltration in the lung tissue. Results of the M. pneumoniae challenge study showed that mice immunized with MUT129 presented with less inflammation, lower detectable number of M. pneumoniae in the lungs when compared with the unimmunized mice. These results indicated that the live attenuated vaccine can efficiently prevent the proliferation of M. pneumonia in the lungs, reduce but not completely prevent the pulmonary inflammatory response. Highlights: An attenuated natural mutant of Mycoplasma pneumoniae (named MUT129 strain) was generated. The attenuated MUT129 strain triggered a strong immune protection against M. pneumoniae infection. This study provide initial evidence for the suitability of MUT129 strain as an attenuated vaccine candidate.